Appendicitis during pregnancy in a Greenlandic Inuit woman; antibiotic treatment as a bridge-to-surgery in a remote area. (18th May 2016) - Dalsgaard Jensen, Trine; Penninga, Luit
Abstract : Appendicitis during pregnancy causes severe diagnostic problems, and is associated with an increase in perforation rate and morbidity compared to that in the normal population. In addition, it may cause preterm birth and fetal loss. In remote areas, appendicitis during pregnancy, besides presenting diagnostic problems, also creates treatment difficulties. In Northern Greenland, geographical distances are vast, and weather conditions can be extreme. We report a case of a Greenlandic Inuit woman who presented with appendicitis during pregnancy. The nearest hospital with surgical and anaesthetic care was located nearly 1200 km away, and, due to extreme weather conditions, she could not be transferred immediately. She was treated with intravenous antibiotic treatment, and after weather conditions had improved, she was transferred by aeroplane and underwent appendicectomy. She recovered without complications. Our case suggests that appendicitis during pregnancy may be treated with antibiotics in remote areas until surgical treatment is available.